Salvage mastectomy for local recurrence and second ipsilateral autologous breast reconstruction using a perforator flap from a different donor site. Issue 1 (1st January 2018) - Homma, Yuki; Satake, Toshihiko; Narui, Kazutaka; Tamanoi, Yoshihiko; Muto, Mayu; Komiya, Takako; Kobayashi, Shinji; Ishikawa, Takashi; Maegawa, Jiro
Abstract: Only one case of second ipsilateral autologous reconstruction for the same breast that had previously undergone reconstruction has been reported. Here we present a patient who underwent breast reconstruction twice using free flap from different donor sites, using a buttock after a local recurrence following the previous reconstruction with a lower abdomen.